A preliminary study of larger surface zooplankton off the Coast Of Terengganu - David Tan Kim Seng (Universiti Pertanian Malaysia, 2012)
From the study carried out there was no significant differences in biomass (wet weight) and the density (animal/m3) among the three stations. The was also no significant differences in the abundance of curstaceans, copepods, chordates, polychaetes and mollusca among the three stations.